Impact of Acute Rejection on Kidney Allograft Outcomes in Recipients on Rapid Steroid Withdrawal - R. L. Heilman; S. Nijim; H. A. Chakkera; Y. Devarapalli; A. A. Moss; D. C. Mulligan; M. J. Mazur; K. Hamawi; J. W. Williams; K. S. Reddy (Journal of Transplantation)
Background. Our aim was to study the impact of clinical acute rejection (CR) and subclinical rejection (SR) on outcomes in kidney transplant recipients treated with rapid steroid withdrawal (RSW). Methods. All patients who received a living or deceased donor kidney transplant and were treated with RSW were included. The primary outcome was death-censored graft survival. Biopsies with Banff borderline changes were included with the rejection groups. Results. 457 kidney transplant recipients treated with RSW were included; 46 (10%) experienced SR, and 36 (7.8%) had CR. Mean HLA mismatch was significantly higher in the CR group. The Banff grade of rejection was higher in the CR group. There was a larger proportion of patients in both rejection groups with the combination of IFTA and persistent inflammation on the follow-up protocol biopsy done at 1 year. The estimated 5-year death-censored graft survival was 81% in SR, 78% in CR, and 97% in the control group (P<.0001). Significant differences were observed in allograft survival between the CR and control group (HR 9.06, 95% CI 3.39–24.2) and between the SR and control group (HR 4.22, 95% CI 1.30–13.7). Conclusion. Both SR and CR are associated with an inferior graft survival in recipients on RSW.